Bacteriological Examination of Drinking Water from Different Sites at a Tertiary Care Hospital Campus of Western India (International Journal of Scientific Research in Science and Technology, 2024)
Introduction: This study presents a detailed investigation into the drinking water quality at campus, focusing on various drinking water sources. Access to safe and clean drinking water is crucial for maintaining public health. In this study, we aimed to assess the drinking water quality at Bhaikaka University campus by collecting and analyzing drinking water samples from various sources. The research focused on identifying the presence of coliform bacteria, particularly E. coli, and evaluating the extent of contamination at different sites. Methodology: A total of 68 drinking water samples were collected from diverse drinking water sources across the campus. The MPN technique was employed to analyze the samples for the presence of coliform bacteria. The sites included all the buildings from the campus of Bhaikaka University. Results: Out of the 68 drinking water samples, 12 samples (17.64%) tested positive for contamination, while 56 samples (82.35%) showed no contamination. The highest number of positive samples (5 out of 15) was observed at Hospital, indicating the need for targeted interventions. Conclusion: This study provides valuable insights into the drinking water quality at campus with the identification of specific sites with higher contamination rates allows for targeted interventions. Future research can build upon these findings to implement effective strategies for sustainable water management on the campus.